The impact of new retail trends in the context of convenience stores - Sousa, Raquel Patrícia Matos (2018)
The convenience retailing sector is being challenged with the threat of new formats from existing competitors, a downward trend in demand and a new type of customer, which is more demanding, empowered and informed. The purpose of this thesis is to study how the newest trends in retail can be adapted to the context of convenience stores located in gas stations, thus increasing shoppers’ intentions to purchase and to visit those stores. To meet this dissertation goal, an empirical research was pursued, in which a Focus Group was conducted as an exploratory and qualitative method. Empirical research was complemented with individual questionnaires for each concept evaluated. Findings show that from an initial bulk of seven trends, only three are positively accepted, two are partially accepted and other two are rejected. Concepts such as Payment with Smartphone, Interactive Screens with Storytelling and Tutorials and Pick-Up Point Lockers received the best feedback and evaluation from the Focus Group participants and proved that must be implemented by retailers in the convenience store sector. Findings also revealed that new concepts to apply in convenience stores must contribute to an automatized store that is able to provide personalized and more convenient services to its customers – the convenience factor proved to be an obligatory factor when innovating in a convenience store. Moreover, concepts that contribute to bring closer the physical and digital world will be appreciated by customers. Today’s customer no longer fears digital innovations in stores, in fact accepts and want stores to have digital features and processes. Subsequently, retailers should acknowledge the impact that new retail trends have on customers’ behavior and intentions toward convenience stores. Furthermore, they must keep in mind that despite the innovation intended, the main goal needs to be to provide convenient experiences and services to the customer.